GERMANIUM AS AN ELEMENT OF CRITICAL RAW MATERIALS. COAL DEPOSITS OF TRANSCARPATTIA – A SOURCE OF GERMANY IN UKRAINE - BURLUTSKYY, Mykola; LYTVYNIUK, Stanislav (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The concept of critical raw materials as it is interpreted in the USA, the European Union and other countries is defined. The main stages of the formation of the regulatory framework and the requirements of the USA and the EU regarding critical raw materials are provided. The chronology of changes in the amount of minerals, which are a component of critical mineral raw materials, is considered. Ukraine is a country with a powerful mineral and raw material base, the riches of its subsoil are determined by the peculiarities of the geological structure of its territory. At the same time, our country is one of the world’s leading producers of some types of minerals, including such important raw materials as manganese, titanium and graphite. There are about 22 critical minerals in our country, which are included, in particular, in the list of critical for the EU. The analysis and prospects of using various methods and modern technologies with the aim of extracting germanium as one of the elements of critical raw materials were carried out. The possibility of using modern extraction methods in Ukraine, in particular for the lignite deposits of Transcarpathia, was considered. At the same time, in Ukraine, it is the lignite deposits of Zakarpattia that have the potential to become an important source for the extraction of rare (rare earth) elements, particularly germanium. The reasons for the involvement of modern world technologies, which would contribute to the production of lignite in Zakarpattia in compliance with all existing ecological and socio-ecological requirements of the current legislation, have been determined. The association of germanium with rare (rare earth) elements in these deposits can increase the economic value of their complex use, since there are foreign technologies that allow simultaneous extraction of several critical elements from one source. The economic expediency of complex coal processing is indicated, taking into account the possibility of obtaining energy and critical elements, in particular germanium. The introduction of leaching and flotation technologies is proposed to increase the efficiency of extraction. This will contribute to the economic growth of the region and meet global requirements for critical raw materials. It is pointed out the need to introduce a Strategy for the extraction of rare earth and rare metals in Ukraine to improve the economic situation in the mining industry, in particular, the need for comprehensive development of lignite deposits, in particular Zakarpattia, with the use of lignite as fuel and rare earth metals as a source of modern technologies in industry.